1981
DOI: 10.1002/iroh.19810660402
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Man‐Induced Eutrophication. Experiences of a Lake Recovery Study in Sweden

Abstract: Recovery of polluted lakes is a complicated process involving many factors. Different lake rehabilitation techniques and former experiences with advanced wastewater treatment and sewage diversion are reviewed. The response in water quality after a nutrient reduction may vary significantly, despite a lowering of the phosphorus concentration in the lake. The different factors influencing the process, such as climatic fluctuations, the growth‐limiting effect of nutrients and phosphorus release from the sediments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…A strong and similar seasonality have been attributed to high retention capacity of shallow lakes throughout world [65,66]. This capacity of retainability of P has been attributed to many factors, primary being the temperature simultaneously coupled with biological processes [64,[67][68][69][70].…”
Section: Resultsmentioning
confidence: 99%
“…A strong and similar seasonality have been attributed to high retention capacity of shallow lakes throughout world [65,66]. This capacity of retainability of P has been attributed to many factors, primary being the temperature simultaneously coupled with biological processes [64,[67][68][69][70].…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorus release from sediment surfaces in contact with or close to well-aerated water can be substantial and much evidence exists from mass balance studies, mainly performed on shallow sewage-loaded lakes (Stevens & Gibson 1977;Ryding & Forsberg 1977;Ryding 1981). Laboratory studies have also confirmed the occurrence of significant aerobic phosphorus release from sediments (Lee et al 1977;Bates & Neafus 1980;Holdren & Armstrong 1980).…”
Section: Categorymentioning
confidence: 92%
“…Sediments are often long−term sources of P to aquatic systems (especially lakes and reservoirs) after external P inputs from the watershed have been reduced or removed (Larson et al, 1979;Ryding, 1981). The flux of P from bottom sediments is often much greater under anaerobic conditions in the hypolimnion of lakes and reservoirs than under aerobic conditions (James et al, 1995).…”
mentioning
confidence: 99%